AN ANALYSIS OF THE LEADING ECONOMIC SECTOR IN SOUTH SULAWESI PROVINCE - Mujahidah (Jurnal Economic Resource, 2020)
The aim of this research is to analyze leading economic sector in south sulawesi province. The method used in this research is Location Quotient Analysis (LQ) and Shift Share Analysis. The research held on july 2020 by using GDRP data of South Sulawesi 2015-2019 period and indonesian GDP data 2015-2019. The result of this research show that in south sulawesi province there 9 economic caterogies which have basic sector namely agriculture, forestry, and fishery: water supply, waste management, waste and recycling; construction, wholesale and retail: car and motorcycle repairment; information and communication: Real Estate; Government administration, defence and sosial security compulsory: Educational Service: Health service and social activity. The result of Shift Share show that the slowest sector in South Sulawesi province is mining and quarrying sector. Whereas, the other 16 sectors are developing sectors.